PRESENTATION OF FINANCIAL STATEMENTS BASED ON ISAK 335 AT THE AT-TANWIR MOSQUE IN THE CITY OF BANJARMASIN - Bahrian Nugroho (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to prepare financial statements for the At Tanwir mosque based on ISAK 335 for the 2024 period by following the accounting cycle process from understanding to presenting financial statements. The type of research used is qualitative descriptive research. The type of data used is secondary data in the form of mosque financial records and mosque profiles created by mosque administrators. The data collection methods used in this study are observation, interviews, and documentation. The results of this study indicate that the At Tanwir Mosque has not yet implemented financial statement presentation in accordance with Financial Accounting Standards Interpretation 335, and its financial records are only kept in a simple manner, recorded in a book and then entered into Microsoft Excel, which contains columns for income and expenses. After preparing the financial statements based on the accounting cycle procedures, it can be seen that the total comprehensive income of the At Tanwir mosque is IDR 48,821,717, while its total net assets are IDR 6,091,967,574,-, and the cash and cash equivalents at the end of the period as of December 31, 2024, amounted to IDR 7,582,782,-.